2016
DOI: 10.3109/08820538.2016.1169302
|View full text |Cite
|
Sign up to set email alerts
|

Does the Stage of Keratoconus Affect Optical Coherence Tomography Measurements?

Abstract: RNFL, macular thicknesses, and ganglion cell parameters in all KC stages were lower than those in the control group. The RNFL, macular thickness, and ganglion cell parameters of the Grade 1 KC group were most similar to those of the control group. The severity of irregular astigmatism at the same stages of KC had a significant effect on OCT measurements. It may therefore be beneficial to know the amount of change/deviation in OCT measurements in keratoconus patients and to report which parameters exceed the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…The results showed that both RNFL and GCC measurements were comparable between the keratoconus and control groups. The control participants had slightly higher global RNFL thickness measurements than the keratoconus participants (106 µm vs. 99 µm and 103 µm vs. 98 µm for the right and left eyes respectively), but these 36 reported that these thickness differences were statistically significant (p < 0.001). Unlike in the present study, Uzunel et al 36 separated their participants with keratoconus (n = 68) into three grades, using the Amsler-Krumeich classification system, and analysed the different mean global RNFL measurements for each grade of keratoconus which may explain this difference.…”
Section: Discussionmentioning
confidence: 91%
“…The results showed that both RNFL and GCC measurements were comparable between the keratoconus and control groups. The control participants had slightly higher global RNFL thickness measurements than the keratoconus participants (106 µm vs. 99 µm and 103 µm vs. 98 µm for the right and left eyes respectively), but these 36 reported that these thickness differences were statistically significant (p < 0.001). Unlike in the present study, Uzunel et al 36 separated their participants with keratoconus (n = 68) into three grades, using the Amsler-Krumeich classification system, and analysed the different mean global RNFL measurements for each grade of keratoconus which may explain this difference.…”
Section: Discussionmentioning
confidence: 91%
“…Among the 360 graft-host sections, confined to only keratoconic eyes in the current study, the most common malapposition was graft step (122 cases, 33.9%). Since it has been reported that preoperative corneal pathology can influence the graft-host apposition patterns, 14,16 we hold the opinion that asymmetrical pre-operative thinning of the cornea in different disease stages caused increased graft step numbers, because the normal corneal grafts from donors were generally thicker than the recipient beds, which had already thinned.…”
Section: Discussionmentioning
confidence: 93%
“…Surprisingly, our results showed no difference in image quality or macular thickness values between scans obtained from uncorrected astigmatic eyes and scans obtained from the same eyes with RGP contact lens correction. A previous study demonstrated that SD‐OCT‐derived parameters such as RNFL or central subfield thickness and mean signal strength were affected by irregular astigmatism 2017. Signal strength was affected significantly by refractive changes already in early stages of keratoconus 2015.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study demonstrated that SD-OCTderived parameters such as RNFL or central subfield thickness and mean signal strength were affected by irregular astigmatism. 7,31 Signal strength was affected significantly by refractive changes already in early stages of keratoconus. 7 In other studies, RNFL thickness changes after astigmatism induction was statistically significant; however, the magnitude of change was minute.…”
Section: Discussionmentioning
confidence: 99%